The Conlara metamorphic complex: Lithology, provenance, metamorphic constraints on the metabasic rocks, and chime monazite dating - López de Luchi, Mónica G. (2021)
The Conlara Metamorphic Complex, the easternmost complex of the Sierra de San Luis, is a key unit to understand the relationship between the late Proterozoic-Early Cambrian Pampean and the Upper Cambrian-Middle Ordovician Famatinian orogenies of the Eastern Sierras Pampeanas. The Conlara Metamorphic Complex extends to the east to the foothills of the Sierra de Comechingones and to the west up the Río Guzmán shear zone. The main rock types of the CMC are metaclastic and metaigneous rocks that are intruded by Ordovician and Devonian granitoids. The metaclastic units comprise fine to medium-grained metagreywackes and scarce metapelites with lesser amounts of tourmaline schists and tourmalinites whereas the metaigneous rocks encompass basic and granitoids rocks. The former occur as rare amphibolite interlayered within the metasedimentary rocks. The granitic component corresponds to a series of orthogneisses and migmatites (stromatite and diatexite). The CMC is divided in four groups based on the dominant lithological associations: San Martin and La Cocha correspond mainly to schists and some gneisses and Santa Rosa and San Felipe encompass mainly paragneisses, migmatites and orthogneisses. The Conlara Metamoprphic Complex underwent a polyphase metamorphic evolution. The penetrative D2-S2 foliation was affected by upright, generally isoclinal, N-NE trending D3 folds that control the NNE outcrop patterns of the different groups. An earlier, relic S1 is preserved in microlithons. Discontinuous high-T shear zones within the schists and migmatites are related with D4 whereas some fine-grained discontinuous shear bands attest for a D5 deformation phase. Geochemistry of both non-migmatitic metaclastic units and amphibolites suggest that the Conlara Metamorphic Complex represents an arc related basin. Maximun depositional ages indicate a pre- 570 Ma deposition of the sediments. An ample interval between sedimentation and granite emplacement in the already metamorphic complex is indicated by the 497 ± 8 Ma age of El Peñon granite. D1-D2 history took place at 564 ± 21 Ma as indicated by one PbSL age calculated for the M2 garnet of La Cocha Group. D3 is constrained by the pervasively solid-state deformed Early Ordovician granitoids which exhibits folded xenoliths of the D1-D2 deformed metaclastic rocks. Pressure-temperature pseudosections were calculated for one amphibolite using the geologically realistic system MnNCKFMASHTO (MnO–Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–Fe2O3). Peak metamophic conditions (M2) indicate 6 kbar and 620 °C. Late chlorite on the rims and in cracks of garnet, along with titanite rims on ilmenite and matrix plagioclase breaking down to albite suggests that the P-T path moved back down. Monazite analyses yield isochron Th–U–Pb ages ranging from 446 to 418 Ma. The oldest age of 446 ± 5 Ma correspond to a migmatite from the Santa Rosa Group. Monazites in samples from the La Cocha and the San Martin group crystallized at decreasing temperatures, followed by the 418 ± 10 Ma low-Y2O3 monazites in one sample of the la Cocha Group that was also obtained from a migmatite, and would likely mark a later stage of a retrograde metamorphism New CHIME monazite ages presented here likely represent post-peak fluid assisted recrystallization that are similar to amphibole and muscovite cooling ages. Therefore the monazite ages may represent a re-equilibration of the monazite on the cooling path of the basement complex.